USO DE TRICHODERMA NATIVO NA PRODUÇÃO DE ALFACE - BARROS FILHO, Luís Gustavo Silva; DA SILVA, Maiele Leandro; STRANG, Rafael de Sá; MUNIZ, Jéssica Gomes; DUARTE, Clara Evelyn de Souza; MODESTO, Emilly Ketlin Queiroz (ANAIS DO ENIC, 2026)
.